Dynamical problems of rigid-elastic systems and structures : IUTAM symposium, Moscow, USSR, May 23-27, 1990 - Banichuk, Nikolai Vladimirovich; Klimov, D. M. (Dmitrii Mikhailovich; Schiehlen, W. O. (Werner O.); International Union of Theoretical and Applied Mechanics; Institut problem mekhaniki (Akademiia nauk SSSR); International Symposium on Dynamical Problems for Rigid-elastic Systems and Structures (1990 : Moscow, R.S.F.S.R.) (Berlin ; New York : Springer-Verlag)
167131